Analisis Faktor-faktor yang Memengaruhi Green Entrepreneurial Intention: Systematic Literature Review - Rahmanto, Andi Adam; Siswandari, Siswandari; Sangka, Khresna Bayu (Universitas Negeri Makassar, 2024)
Increased awareness of the negative impact of human activities on the environment has led to a growing interest in green entrepreneurship. This study aims to investigate the factors that influence green entrepreneurial intentions among the younger generation. The method used in this study is Systematic Literature Reviews (SLR). The results showed that environment, entrepreneurship education, institutional and state support, and psychological factors such as self-efficacy influence green entrepreneurial intentions. In addition, social support and perceived happiness were also found to have a relationship with the intention to start a green venture.